Analisis Lama Mencari Kerja Dan Lama Mempersiapkan Usaha Tenaga Kerja Terdidik Di Sumatera Barat : Peran Pendidikan Dan Dampak Upah - Elyn Wulandari; Joan Marta (Universitas Negeri Padang, 2022)
This study aims to analyze the difference between the length of time looking for work and the length of time to prepare a business for the workforce who are already working in terms of education level, wages, age, gender, work experience, training, marital status, and area of residence. The total unit of analysis used is 666 individual samples sourced from the August 2020 Labor Force Survey (SAKERNAS) data for the West Sumatra Province. The analytical method used is Poisson regression. The results of the Poisson regression show that the higher the level of education, the opportunities to find work and the opportunity to prepare for a business will be longer than the level of education below high school. The results of this study also show that wages/salaries equally affect the opportunity to look for work and the time to prepare for a business in West Sumatra Province.